Female knowhow: legitimation of male knowledge - Assumpta Rigol Cuadra (Universidad de Alicante, 2012)
The assigning of devaluating categories towards certain professions related to caring, due to the reproduction of tasks traditionally carried out within domestic and private areas, has to do with the configuration of a masculine social order which needed a throughout history process of devaluating and silencing the contribution made by women, and the creation of arbitrary assumptions based on biology, in order to justify their exclusion. The monopoly of the health field and its control by Medicine through the creation of Institutions entitled to legitimate and pass the knowledge on, has permitted to leave certain healing practices out of Science, such as the ones carried out by nurses and midwifes. It is therefore necessary to rewrite history, to recall from oblivion those women and professions that made important contributions but do not appear in the official history and have been relegated from knowledge for control and power interests. Given the Science is not neutral, it is necessary to point out the strategies used for the reproduction and survival of the assumptions on which the system of social classification is based.